904 Active school transportation and stroller use in Kindergarten children in Toronto, Canada. (1st September 2016) - Rothman, Linda; Macpherson, Alison; Howard, Andrew; Parkin, Patricia; Richmond, Sarah A; Birken, Catherine S
Abstract : Background: Declines in child pedestrian motor vehicle collisions have occurred over the past 20 years possibly due to the simulaneous decline in children walking to school. Active school transportation (AST) is a form of physical activity that should be encouraged as all children make the daily school commute. Little is known about AST in kindergarten students (4–5 years). Young children may travel to school by sedentary means such as by car, stroller or wagon, due to parental concerns regarding traffic safety; however, recent recommendations by several professional associations have discouraged stroller use due to concerns their use may lead to reduced physical activity. Methods: School transportation modes for kindergarten students were compared to those of students of all ages. Observational transportation mode counts were conducted in two samples in May-June 2015 at kindergarten-grade 6 schools in Toronto, Canada: 1) outside of schools with separate kindergarten entrances (n = 26 schools); 2) at optimal viewing locations for all-age students (n = 100 schools). Proportions of children arriving by different modes were compared between samples using Chi–square statistics. Results: The use of active modes was significantly lower in the kindergarten sample (n = 26 schools) compared to those in the all-age sample (n = 100 schools); 60% versus 74%, Chi-square = 91.37, p < 0.001. The predominant sedentary travel mode was by car (38%). The proportion of kindergarten children arriving by stroller or wagons was 1.8%. Conclusions: Strollers and wagons were not generally used for school travel by kindergarten students. Observed AST was significantly lower in kindergarten students compared to all ages. The overuse of cars for school travel for young children requires further examination to reduce sedentary behaviour and to decrease vehicle traffic around schools which puts all child pedestrians at increased risk for injury.